The Effect of Grazing Intensities on Magnesium Contents - Czeglédi, Levente; Győri, Zoltán; Kovács, Béla; Prokisch, József; Béri, Béla (Acta Agraria Debreceniensis, 2004)
Research was carried out on two areas of grassland in Hortobágy National Park, Hungary. Two herds of Hungarian Grey Cattle were kept in free range grazing and the effects of grazing pressure on the magnesium content of soil and ryegrass (Lolium perenne L) were determined. Changes of plant available and total soil magnesium content under different grazing intensities did not show any evident tendency on the investigated grasslands. Different amounts of cattle faeces, urine and trampling had no effect on the magnesium concentration of ryegrass. We conclude that the magnesium content of ryegrass on both grassland sites as moderate grazing and overgrazing matches the requirements of cattle. Symptoms of magnesium deficiency of cattle will likely not appear.